2004
DOI: 10.1002/cd.110
|View full text |Cite
|
Sign up to set email alerts
|

How children and adults learn to use computers: A developmental approach

Abstract: What is the relation between information technology and human development? This is one of the big questions for contemporary developmental scientists. An enormous research literature has documented how information technologies shape human development cognitively (Papert, 1980(Papert, , 1993, socially (Turkle, 1984(Turkle, , 1995, and physically (Harwin and Haynes, 1992). However, how human beings, particularly ordinary children and adults, master information technology cognitively (understanding the Internet, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 83 publications
1
7
0
Order By: Relevance
“…We also found the idea that the adults' difficulty of learning using the computer is rather a myth supported by daily life anecdotes and not by empirical evidence (Yan & Fischer, 2004).…”
Section: Age and Experience In Using The Computermentioning
confidence: 58%
See 1 more Smart Citation
“…We also found the idea that the adults' difficulty of learning using the computer is rather a myth supported by daily life anecdotes and not by empirical evidence (Yan & Fischer, 2004).…”
Section: Age and Experience In Using The Computermentioning
confidence: 58%
“…We suppose that the participants, when they learned by themselves or occasionally helped by friends how to use a computer, before studying it at school, used strategies based on trial and error, in contrast to learning in the group-class which are characterized by scaffolding (Yan & Fischer, 2004) and sharing team tacit knowledge (Zhang, de Pablos, & Zhu, 2012). The two acquisition ways may have different consequences over the emotions, beliefs and attitudes towards the computer and the internet.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the age and gender differences, there are also cultural differences in attitudes towards and methods of interacting with computers, including browsing websites, using search engines and menus and communicating online (see review by Yan and Fischer 2004).…”
Section: Influence Of Individual Characteristics On Exposurementioning
confidence: 99%
“…Proportional head mass is also a developmental difference between adults and children and it has been suggested that this may affect the physical ramifications for children viewing different display heights (Straker et al 2008a). Yan and Fischer (2004) reviewed the literature concerning cognitive and social differences in learning to use computers and concluded that very little was known about developmental differences between children and adults in this context. It is reasonable to assume, however, that social and cognitive immaturity may offer less protection for children compared to adults when interacting with the computer.…”
Section: Children Are Different To Adults Physically Cognitively Somentioning
confidence: 99%
“…56 CIPA fails to recognize that children as individual users are active processors of information and that children of different ages are going to be affected in divergent ways by filtering programs. 57 Younger children benefit from more restrictive filters while older children benefit from less restrictive filters.…”
Section: Reasons For More Limited Implementation In Librariesmentioning
confidence: 99%